2011
DOI: 10.1007/s10826-011-9520-x
|View full text |Cite
|
Sign up to set email alerts
|

Parent, Teacher and Student Cross Informant Agreement of Behavioral and Emotional Strengths: Students With and Without Special Education Support

Abstract: Information from multiple sources is recommended when assessing students' emotions and behaviors. Relatively few studies about cross informant agreement of behavioral and emotional strengths exist, especially for students with special education needs. The purpose of this study was to extend the cross informant agreement research of the Behavioral and Emotional Rating Scale (BERS-2) with a sample of Finnish parents, teachers and students. First, we studied the cross informant agreement of students' behavioral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…The overall strengths index comprises four subscales: Interpersonal Strengths (15 items; e.g., Badmits mistakes^), Family Involvement (10 items; Btrusts a significant person with his/her life^), Intrapersonal Strengths (11 items; Bdemonstrates a sense of humor^), and Affective Strengths (7 items; Bexpresses affection for others^). The BERS-2 was developed to be broadly applicable, and recently, scholars have successfully used this questionnaire in research on children with disabilities (e.g., Dieleman et al 2018b;Sointu et al 2012). Cronbach α's ranged from 0.92 (ASD) to 0.96 (NO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall strengths index comprises four subscales: Interpersonal Strengths (15 items; e.g., Badmits mistakes^), Family Involvement (10 items; Btrusts a significant person with his/her life^), Intrapersonal Strengths (11 items; Bdemonstrates a sense of humor^), and Affective Strengths (7 items; Bexpresses affection for others^). The BERS-2 was developed to be broadly applicable, and recently, scholars have successfully used this questionnaire in research on children with disabilities (e.g., Dieleman et al 2018b;Sointu et al 2012). Cronbach α's ranged from 0.92 (ASD) to 0.96 (NO).…”
Section: Methodsmentioning
confidence: 99%
“…Two examples are the degree to which a child can express affection in close relationships or respond adaptively to distress in others by expressing concern or offering comfort. Recent studies suggested that the BERS-2 (Epstein 2004) is a promising instrument to assess psychosocial strengths in children with heterogeneous disabilities, including those with DS (e.g., Dieleman et al 2018b;Sointu et al 2012). Notably, this research on psychosocial strengths in children also highlighted important variation in the presentation of behavioral and emotional strengths among children with and without special needs (e.g., Dieleman et al 2018b).…”
mentioning
confidence: 92%
“…Some commonly held reasons for discrepancies in multi-informant responses are relatively strong within-observer effects that are often stronger than the inter-observer effects [18,65,66] and children's behaviours being situation-specific [23,25,67]. Of these, the relatively strong within-observer associations have been observed in studies across various domains of children's behavioural studies.…”
Section: Plos Onementioning
confidence: 99%
“…Afinal, é no ambiente estruturado de atividades programadas que os comportamentos destoantes dos parâmetros da normalidade tenderão a ficar em evidência. (Bierman, 2011;Curtis Pisecco, Hamilton, & Moore , 2006;Farmer et al, 2011;Roig, 2011;Rudasill, Reio, Stipanovic, & Taylor, 2010;Sointu, Savolainen, Lappalainen, & Epstein, 2012).…”
Section: Participantesunclassified